2022
DOI: 10.5194/cp-18-1509-2022
|View full text |Cite
|
Sign up to set email alerts
|

Influence of long-term changes in solar irradiance forcing on the Southern Annular Mode

Abstract: Abstract. The Southern Annular Mode (SAM) is the leading mode of climate variability in the extratropical Southern Hemisphere, with major regional climate impacts. Observations, reconstructions, and historical climate simulations all show positive trends in the SAM since the 1960s; however, earlier trends in palaeoclimate SAM reconstructions cannot be reconciled with last millennium simulations. There are also large differences in the magnitude of solar irradiance change between various solar reconstructions, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 79 publications
1
9
2
Order By: Relevance
“…Volcanic signals have likewise been a challenge to detect in Southern Hemisphere temperature reconstructions 97 . Some studies have proposed that an observed relationship between SAM and ENSO 48 , 93 , 98 100 could provide a pathway for solar forcing 101 to influence the SAM 50 , 102 ; however, our results do not support this mechanism during the the Common Era. In a set of model simulations, Wright et al 102 found that increasing the amplitude of the prescribed solar variability lead to a significant relationship between solar forcing and the simulated SAM.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Volcanic signals have likewise been a challenge to detect in Southern Hemisphere temperature reconstructions 97 . Some studies have proposed that an observed relationship between SAM and ENSO 48 , 93 , 98 100 could provide a pathway for solar forcing 101 to influence the SAM 50 , 102 ; however, our results do not support this mechanism during the the Common Era. In a set of model simulations, Wright et al 102 found that increasing the amplitude of the prescribed solar variability lead to a significant relationship between solar forcing and the simulated SAM.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies have proposed that an observed relationship between SAM and ENSO 48 , 93 , 98 100 could provide a pathway for solar forcing 101 to influence the SAM 50 , 102 ; however, our results do not support this mechanism during the the Common Era. In a set of model simulations, Wright et al 102 found that increasing the amplitude of the prescribed solar variability lead to a significant relationship between solar forcing and the simulated SAM. These authors suggest that using high amplitude solar forcing could help reconcile SAM reconstructions with climate simulations; however, the lack of solar signals in our reconstruction differs notably from their findings and instead further supports the realism of low-amplitude solar forcing scenarios 103 105 .…”
Section: Discussioncontrasting
confidence: 99%
“…On the East Antarctic Plateau, SAM phase and surface temperature are anti-correlated because a positive SAM phase is associated with a reduced meridional heat transport (Marshall and Thompson, 2016), and the SAM signature is found in the temperature at the ABN site, although its effect on δ 18 O is less prominent (Servettaz et al, 2020). The variability of SAM is linked to other climate modes and parameters such as El Niño -Southern Oscillation (Abram et al, 2014), Atlantic Meridional Overturning Circulation (Pedro et al, 2018) and solar irradiance (Wright et al, 2022). On the time scale of a thousand years, the SAM has been reconstructed from paleoclimate proxies sensitive to SAM-related temperature anomalies (Abram et al, 2014;Dätwyler et al, 2018).…”
Section: Atmospheric Teleconnectionsmentioning
confidence: 99%
“…On the time scale of a thousand years, the SAM has been reconstructed from paleoclimate proxies sensitive to SAM-related temperature anomalies (Abram et al, 2014;Dätwyler et al, 2018). The two reconstructions yielded similar trends, although the reconstruction of Abram et al (2014) shows more amplitude due to being calibrated on the instrumental period with annual SAM indices (Wright et al, 2022). Here we will only show the annual SAM reconstruction from (Dätwyler et al, 2018;Fig.…”
Section: Atmospheric Teleconnectionsmentioning
confidence: 99%
“…Other known solar cycles such as the 100, 200, 500, and 1,000‐year cycles have been observed in both TSI constructions and various Holocene paleoclimate records (Poore et al., 2004; Steinhilber et al., 2012; Xu et al., 2014; Zhao & Feng, 2015). Models and proxy data show that the Southern Westerly Winds (SWW), a mid‐latitude wind and precipitation belt, also react to TSI variations in the same manner as tropical precipitation during the Late Holocene, shifting poleward when TSI increases, and equatorward when TSI decreases, with responses exceeding the range of system internal variability (Varma et al., 2011; Wright et al., 2022). However, no proxy or observational record thus far has demonstrated the relative importance of the full suite of proposed solar cycles within the SWW nor have they had the temporal resolution to reconstruct cycle evolution over the entirety of the Holocene period.…”
Section: Introductionmentioning
confidence: 99%